Microclimate management in libraries: A systematic literature review - Syam'aeni, Muhammad Asyep; Wibowo, Muhamad Prabu; Salim, Tamara Adriani (Record and Library Journal, 2025)
Background of the study: Increasingly extreme climate change requires libraries to develop microclimate management strategies to maintain valuable ecosystems. Purpose: This study aims to systematically review the literature on best practices for microclimate management in libraries, with a particular focus on temperature and humidity control. Method: Utilizing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, this study screened and analyzed 25 scientific articles published between 2014 and 2024. Findings: The results of this study show that maintaining microclimate stability in libraries requires an integrated approach combining HVAC systems, ventilation strategies, and monitoring technologies. Automated control systems and natural ventilation strategies both play critical roles in achieving effective microclimate management tailored to the specific conditions of each library. Conclusion: Microclimate management in libraries is crucial for ensuring the long-term preservation of collections. Effective strategies tailored to local conditions not only safeguard valuable materials but also contribute to the sustainability of the storage environment. These findings emphasize the importance of integrating appropriate technologies and methods to support the continued conservation of library resources.